Almost a Family, Practically Related: Questions on Sumerian Kinship Terminology - Andrea Rebecca Marrocchi Savoi (Papers from the Institute of Archaeology, 2022)
The aim of this paper is to investigate some aspects of fictive kinship in ancient Sumer that we find out through administrative, legal and literary texts. From the Neo-Sumerian period several texts of different nature have survived, which constitutes a breeding ground for this kind of study. In anthropological studies the kinship terminology is considered fundamental to understand the structure and dynamics of human societies. It seems that, both in Sumerian and in Akkadian, the terms of kinship are reduced to the first kinship degree, and are not used to express different relationships, but they are unambiguous. Some scholars (Civil 1974; Götzelt 1995) tried to compare Sumerian terminology with other better-known systems, but the results are discordant due to the complexities of documentation and language. Considering that most attested terms express just the first degree of kinship, we can assume that in Sumerian the juxtaposition of primary terms is used to express the most distant relationships on the family tree. A lot of kinship’s terms appears in the texts, some of that, probably, used also outside familial context. Perhaps in the workplace the family structure and terminology were adopted symbolically practically, which makes it more difficult to interpret some legal texts, as the so called di-til-la, because the ambiguity of terms makes the interpretation unclear. It is necessary to use an interdisciplinary approach through philology and anthropology to enlighten as much information as possible from the texts.